Enhanced T-Cell Immunity to Osteosarcoma Through Antibody Blockade of PD-1/PD-L1 Interactions. Issue 3 (April 2015) - Lussier, Danielle M.; O'Neill, Lauren; Nieves, Lizbeth M.; McAfee, Megan S.; Holechek, Susan A.; Collins, Andrea W.; Dickman, Paul; Jacobsen, Jeffrey; Hingorani, Pooja; Blattman, Joseph N.
Abstract : Osteosarcoma is the most common bone cancer in children and adolescents. Although 70% of patients with localized disease are cured with chemotherapy and surgical resection, patients with metastatic osteosarcoma are typically refractory to treatment. Numerous lines of evidence suggest that cytotoxic T lymphocytes (CTLs) limit the development of metastatic osteosarcoma. We have investigated the role of PD-1, an inhibitory TNFR family protein expressed on CTLs, in limiting the efficacy of immune-mediated control of metastatic osteosarcoma. We show that human metastatic, but not primary, osteosarcoma tumors express a ligand for PD-1 (PD-L1) and that tumor-infiltrating CTLs express PD-1, suggesting this pathway may limit CTLs control of metastatic osteosarcoma in patients. PD-L1 is also expressed on the K7M2 osteosarcoma tumor cell line that establishes metastases in mice, and PD-1 is expressed on tumor-infiltrating CTLs during disease progression. Blockade of PD-1/PD-L1 interactions dramatically improves the function of osteosarcoma-reactive CTLs in vitro and in vivo, and results in decreased tumor burden and increased survival in the K7M2 mouse model of metastatic osteosarcoma. Our results suggest that blockade of PD-1/PD-L1 interactions in patients with metastatic osteosarcoma should be pursued as a therapeutic strategy.